Intensity of exposure to a patient activation intervention and patient engagement in medical visit communication. Issue 7 (July 2017) - Ibe, Chidinma; Bowie, Janice; Roter, Debra; Carson, Kathryn A.; Lee, Bone; Monroe, Dwyan; Cooper, Lisa A.
Highlights: We trained community health workers (CHWs) to deliver a patient activation intervention. We examined the relationship between intervention exposure and patients' medical communication. Patients who discussed more topics related to the activation protocol were more likely to ask psychosocial-related questions. Patients who had longer CHW sessions used more facilitative communication. CHWs were effective at delivering a patient activation intervention. Abstract: Objective: We examined associations between intensity of exposure to a community health worker (CHW) delivered communication activation intervention targeting low-income patients with hypertension. Methods: We analyzed question-asking behaviors of patients assigned to the intervention arms (n = 140) in a randomized controlled trial. Intensity of exposure to the intervention was operationalized as the duration of face-to-face coaching and number of protocol-specified topics discussed. Mixed effects models characterized the relationship between intensity of exposure and patients' communication in a subsequent medical visit. Results: The number of topics discussed during the coaching session was positively associated with patients' asking psychosocial-related questions during their visit. The duration of the coaching session was positively associated with patients' use of communication engagement strategies to facilitate their participation in the visit dialogue. Exposure to a physician trained in patient-centered communication did not influence these relationships. Conclusions: A dose-response relationship was observed between exposure to a CHW- delivered communication activation intervention and patient-provider communication. Practice implications: This study supports the use of CHWs in activating patients toward greater communication in the therapeutic exchange.